Accuracy of different handgrip values to identify mobility limitation in older adults. (May 2021) - Delinocente, Maicon Luís Bicigo; de Carvalho, Danilo Henrique Trevisan; Máximo, Roberta de Oliveira; Chagas, Marcos Hortes Nisihara; Santos, Jair Licio Ferreira; Duarte, Yeda Aparecida de Oliveira; Steptoe, Andrew; de Oliveira, Cesar; Alexandre, Tiago da Silva
Highlights: Handgrip < 32 kg was the best cutoff point to identify mobility limitation in men. Handgrip < 21 kg was the best cutoff point to identify mobility limitation in women. Handgrip < 32 kg for men has 49.1% sensitivity, 79.8% specificity and AUC of 0.82. Handgrip < 21 kg for women has 58.6% sensitivity, 72.9% specificity and AUC of 0.83. Abstract: Background/Objective: Mobility limitation is commonly the first sign of impaired physical function and predisposes older adults to disability. Moreover, recent epidemiological studies have classified neuromuscular strength as the best explanator of mobility limitation. However, existing cutoffs have not been adequately analyzed regarding accuracy. Therefore, our aims were to define and compare the accuracy of different cutoff points of handgrip strength for the identification of mobility limitation. Methods: Cross-sectional study with 5783 participants from the SABE (Saúde, Bem-Estar e Envelhecimento [Health, Wellbeing and Aging]) and ELSA (English Longitudinal Study of Ageing) cohorts aged 60 years or older. Handgrip strength was measured using a dynamometer. Walking speed <0.8 m/s was considered mobility limitation. Receiver operating characteristic curves and probabilities of presenting mobility limitation were calculated. Results: Handgrip strength <32 kg for men and <21 kg for women demonstrated good diagnostic accuracy for mobility limitation, with 49.1% sensitivity and 79.8% specificity for men and 58.6% sensitivity and 72.9% specificity for women. The fully adjusted models had an area under the curve of 0.82 for men and 0.83 for women, with odds of presenting mobility limitation of 1.88 [95% CI: 1.50 – 2.37] for men and 1.89 [95% CI: 1.57 - 2.27] for women. Conclusions: The results of this study support the accuracy of handgrip strength as a clinical marker of mobility limitation. Furthermore, manual dynamometry is easily incorporated into clinical practice, has a good cost-benefit, besides being a simple, valid, reliable and effective method for use in both the scientific community and outpatient practice.